Assessing the Viability of the 2005 Protocol to the Convention for the Suppression of Unlawful Acts against the Safety of Maritime Navigation - Hamid, Abdul Ghafur@Khin Maung Sein; Kyaw Hla Win @ Md. Hassan Ahmed, Hassan (AENSI Publications, 2012)

(untitled)
The terrorist attack on the Achille Lauro prompted the international community to adopt the Convention for the Suppression of Unlawful Acts against the Safety of Maritime Navigation (SUA) 1988, which established a legal basis for prosecuting maritime violence that did not fall within the piracy framework of the United Nations Convention on the Law of the Sea 1982. To extend the range of offences covered by the Convention, it was amended by the 2005 Protocol. The Protocol, however, has been the subject of much criticism. One of the most serious criticisms of the Protocol is directed at its Article 8bis, which authorizes a state party to visit a ship flying the flag of another state party without prior authorization from the flag state on the ground of failure to respond within four hours. In fact, this provision is in conflict with the exclusive jurisdiction of a flag state over a ship flying its flag on the high seas. This is the reason why although the 2005 Protocol entered into force on 28 July 2010, until present, there are only 22 States parties, most of which are not major maritime countries. The main objective of this paper therefore is to identify shortcomings of the 2005 Protocol and assess its viability. It is suggested that the 2005 Protocol needs to be revised to cure its deficiencies in order to attract more states to become parties to it.